Warna Lokal Batak Angkola Dalam Novel “Azab Dan Sengsara” Karya Merari Siregar - Fitrah, Yundi (UI Scholars Hub, 2008)
This writing tells about the variation of Bataknese cultural of Angkola on torture and misery novel. Since Indonesia literature was born. The variation of culture always enrich it. The variation of culture especially visible on novel, the some likes torture and misery in Merari Siregar which is coloured by Bataknese of Angkola. The variation of Bataknese culture of Angkola on the novel, such as position of clan and the system of arrangement, tradition of martandang (visiting to girl’s house), belief to native doctor and soul of human being that was die, and the system of division of belongings.